Network disaggregation fundamentals LiveLessons video training (LiveLessons., 2019)
"The Rough Cuts/Sneak Peek program provides early access to Pearson products and is exclusively available to Safari subscribers. Content for titles in this program is made available throughout the development cycle, so products may not be complete, edited, or finalized, including post-production editing."--Resource description page